Burden of Respiratory Syncytial Virus Associated Severe Pneumonia in Hospitalized Children - Madhusha Gonapaladeniya; Thushari Dissanayake; Guwani Liyanage (International Journal of Pediatrics)
Respiratory syncytial virus (RSV) is a leading cause of severe respiratory infections. We examined the burden of RSV-associated severe community-acquired pneumonia among hospitalized children and factors that predict RSV etiology. A hospital-based prospective study examined children below five years of age admitted with radiologically confirmed severe or very severe pneumonia in two tertiary care centers in Sri Lanka. Nasopharyngeal secretions (NPS) were tested for 19 viruses by multiplex RT-PCR. Univariate and multivariate analysis was performed to determine whether RSV etiology could be predicted based on clinical, sociodemographic, environmental, radiological, and laboratory parameters. A total of 108 children with severe or very severe were included in the study. At least one virus was found in NPS in 92.5% of children. Forty-six children had RSV (+) pneumonia. Mean RSV proportion was 42.6% (95% CI: 33.1-52.5%, p value = 0.149). RSV as a single virus was found in 41.3% (19/46). The children with RSV (+) pneumonia were younger (p=0.026) and had lower C-reactive protein (p=0.003) and household crowding (p=0.012) than the RSV (-) group, after controlling for confounding covariates. In conclusion, the present study demonstrated that respiratory syncytial virus was the commonest virus associated with CAP in children under five years. Younger age, crowded housing, and lower C-reactive protein levels were predictors of severe RSV-associated pneumonia.